(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This article examines the theoretical and practical aspects of strengthening military patriotism in the context of modern geopolitical instability and hybrid threats. The study analyzes patriotism not only as a moral value, but also as a critically important cognitive resource and a “force multiplier” that ensures national security. Using the strategic experience of Uzbekistan as an example, the article explores the integration of historical heritage with modern military educational technologies. Furthermore, it proposes strategic approaches aimed at ensuring cognitive security and strengthening the unity between the army and the people within an increasingly digitalized global environment.